Consciousness, mindfulness, and introspection: integrating first- and second-person phenomenological inquiry with experimental and EEG data to study the mind - Milicevic, Anita; Blazely, Angela; Bragin, Anatol; Dunseath, Ross W. J.; Matiasz, Nicholas J.; Ribeiro, Mauricio Watanabe; Sardeto Deolindo, Camila; Kozasa, Elisa H.; Wallace, B. Alan (Frontiers in Psychology, 2025)
Studies on consciousness need to develop further a mixed methods research design that effectively integrates first-, second- and third-person research approaches. Mixed methods research has not fully explored the methodological potential of the participant–observer role and the interdependence of knowledge across disciplines to gain a deeper understanding of such inquiries. This paper describes a theoretical and methodological framework that integrates phenomenological, psychological, and electrophysiological methods for the study of consciousness and the mind. This methodological approach includes the purposive sampling of contemplative practitioners extensively trained to observe their mental states and processes with sustained attention, mindfulness, and introspection. By reporting the theoretical and methodological framework here, it is anticipated that the authors' experience of having used this in a small pilot study will offer valuable guidance to fellow researchers seeking to maximize the rigor of their in-depth studies on consciousness and the mind.